2021
DOI: 10.1016/j.anr.2021.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Virtual Reality Simulation Program Regarding High-risk Neonatal Infection Control on Nursing Students

Abstract: Virtual reality simulation can give nursing students a safe clinical experience involving highrisk infants where access to neonatal intensive care units is limited. This study aimed to examine the effects of a virtual reality simulation program on Korean nursing students' knowledge, performance selfefficacy and learner satisfaction. Methods: A nonequivalent control group design was applied. Senior nursing students were divided into an experimental group (n ¼ 25) experiencing virtual reality simulation and rout… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
68
1
10

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(103 citation statements)
references
References 35 publications
(45 reference statements)
5
68
1
10
Order By: Relevance
“…Nursing students need to experience nursing in actual clinical settings, but they get limited opportunities to personally observe and practice COVID-19-related infection control nursing, as well as acquire sufficient nursing skills. In particular, practicing pediatric nursing, including care of infants, is even more challenging due to the increased vulnerability of the child to infection [ 4 ]. Therefore, college instructors need to develop curricula to enable nursing students to cope with infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…Nursing students need to experience nursing in actual clinical settings, but they get limited opportunities to personally observe and practice COVID-19-related infection control nursing, as well as acquire sufficient nursing skills. In particular, practicing pediatric nursing, including care of infants, is even more challenging due to the increased vulnerability of the child to infection [ 4 ]. Therefore, college instructors need to develop curricula to enable nursing students to cope with infectious diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, a large gathering of students should be avoided in the middle of a pandemic to avoid the risk of viral transmission, and thus, new training methods should be applied. Accordingly, nursing training programs using advanced technologies are being developed [ 5 ], including a growing trend in virtual reality (VR) [ 4 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Accordingly, various studies have been conducted, such as an integrative review study centered on experimental research that was conducted from 2016 to 2019 to confirm the effect of nursing education using VR, and performance, self-confidence, and learning satisfaction were significantly improved [ 6 ]. In addition, a recent experimental study showed that the experimental group that performed VR simulations to provide safe clinical expiration of neonatal intensive care units with limited access to nursing students had a higher high-risk neural infrastructure self-efficacy and learner status than the control group [ 7 ].…”
Section: Research Needsmentioning
confidence: 99%